Obesidade e COVID-10: Impacto na Imunidade, Infecção e Vacinação - Assolini, João Paulo (Revista de Epidemiologia e Controle de Infecção, 2023)
Obesity is a complex and multifactorial pathology that has been increasing significantly in recent decades, becoming a serious public health problem. It can be characterized by an energy and metabolic imbalance that compromises the health of individuals. Obesity can be complicated by other diseases or be associated with the development of comorbidities, such as diabetes mellitus, cardiovascular disease, hypertension, dyslipidemia, hepatic steatosis, in addition to various types of cancer.1